2021
DOI: 10.1136/heartjnl-2020-318726
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning model for predicting out-of-hospital cardiac arrests using meteorological and chronological data

Abstract: ObjectivesTo evaluate a predictive model for robust estimation of daily out-of-hospital cardiac arrest (OHCA) incidence using a suite of machine learning (ML) approaches and high-resolution meteorological and chronological data.MethodsIn this population-based study, we combined an OHCA nationwide registry and high-resolution meteorological and chronological datasets from Japan. We developed a model to predict daily OHCA incidence with a training dataset for 2005–2013 using the eXtreme Gradient Boosting algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Meanwhile, the model got a Mean Absolute Percentage Error (MAPE) of 3.369%, and R 2 was 0.948. Studies have shown that when MAPE is less than 10%, the model fit is better ( Nakashima et al, 2021 ), so the ARIMA price prediction model is feasible.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the model got a Mean Absolute Percentage Error (MAPE) of 3.369%, and R 2 was 0.948. Studies have shown that when MAPE is less than 10%, the model fit is better ( Nakashima et al, 2021 ), so the ARIMA price prediction model is feasible.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] Work by Nakashima et al allowed highly precise estimates of risk for out-ofhospital cardiac arrests using a ML model. 27 Although few, studies in the in-patient setting are nevertheless promising. Zhang et al integrated AI with their hospital management system to analyse 14 clinical variables and predict in real-time the risk of major adverse cardiac events in patients presenting with chest pain.…”
Section: Ai In Clinical Cardiology and Daily Life Clinical Decision S...mentioning
confidence: 99%
“…Advancing research along these lines, in 'A machine learning model for predicting the out-of-hospital cardiac arrest using meteorological data,' Nakashima et al 3 employ a novel approach to predict the incidence of out-of-hospital cardiac arrest (OHCA) in Japan. The analysis combines data from the All-Japan Utstein Registry of OHCA cases with high-resolution meteorological and chronological data to predict daily OHCA incidence based on weather patterns.…”
Section: David Foster Gaieskimentioning
confidence: 99%